Correlation Between Spirituality Levels and Depression among First-Year Students in Health Science Programs - Fitriani, Dwi Rahmah; Asrianti, Ulfa Dwi; Asthiningsih, Ni Wayan Wiwin (Genius Journal, 2025)
Introduction: Depression is a common mental health issue among first-year university students, often resulting from the challenges of adapting to new academic and social environments. Spirituality is considered a protective factor that may help reduce symptoms of depression by promoting emotional resilience and a sense of meaning. Objective: This study aimed to examine the relationship between spirituality levels and depression among first-year students enrolled in health study programs at Muhammadiyah Universitas Muhammadiyah Kalimantan Timur. Additionally, the study analyzed the distribution of spirituality and depression levels and explored demographic characteristics that may influence this relationship. Methods: A descriptive correlational study with a quantitative approach was conducted using stratified random sampling. The sample consisted of 271 freshmen, determined using the Slovin formula. Data collection instruments included the Daily Spiritual Experience Scale (DSES) to assess spirituality levels and the Depression Anxiety Stress Scale (DASS-21) to measure depression. Data were analyzed using the Spearman rank correlation test. Results: The analysis revealed a significant negative correlation between spirituality and depression (p = 0.000; r = -0.406), indicating that higher levels of spirituality were associated with lower levels of depression. The strength of the correlation was moderate. Conclusion: The study found a significant negative correlation between spirituality and depression among freshmen in health-related study programs. Higher levels of spirituality were associated with lower levels of depression, highlighting the potential protective role of spiritual well-being in supporting student mental health.